2015
DOI: 10.1007/s11356-015-5420-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of selected anti-cancer drugs on the induction of DNA double-strand breaks and changes in gene expression in human hepatoma HepG2 cells

Abstract: In chemotherapy, various anti-cancer drugs with different mechanisms of action are used and may represent different risk of undesirable delayed side effects in treated patients as well as in occupationally exposed populations. The aim of the present study was to evaluate genotoxic potential of four widely used anti-cancer drugs with different mechanisms of action: 5-fluorouracil (5-FU), cisplatin (CDDP) and etoposide (ET) that cause cell death by targeting DNA function and imatinib mesylate (IM) that inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 85 publications
(82 reference statements)
1
7
0
Order By: Relevance
“…5-FU was applied in a dose range not causing cellular injury to focus on direct, cell specific effects. The applied 5-FU doses were in line with previous studies of Novak et al [44] and Gajski et al [45], who also found that doses up to 250 µM are nontoxic for HepG2 cells. Also for analyzing the effect of 5-FU in primary human hepatocytes, a dose was chosen in accordance with previous studies showing that it does not affect hepatocellular viability [46] For in vivo analyses, we administered a single dose of 200 mg/kg 5-FU to mice.…”
Section: Discussionsupporting
confidence: 90%
“…5-FU was applied in a dose range not causing cellular injury to focus on direct, cell specific effects. The applied 5-FU doses were in line with previous studies of Novak et al [44] and Gajski et al [45], who also found that doses up to 250 µM are nontoxic for HepG2 cells. Also for analyzing the effect of 5-FU in primary human hepatocytes, a dose was chosen in accordance with previous studies showing that it does not affect hepatocellular viability [46] For in vivo analyses, we administered a single dose of 200 mg/kg 5-FU to mice.…”
Section: Discussionsupporting
confidence: 90%
“…Target chromone/furoxan hybrids (12a-d, 13a-d, 14a-d and 15ad) were evaluated for their inhibitory effects against five different human cancer cell lines (hepatoma HepG2, breast carcinoma MCF-7, colorectal carcinoma HCT-116, melanoma B16 and chronic myeloid leukaemia K562), with the reference fluorouracil (5-Fu) [63][64][65][66] . Meanwhile, the activities against the human normal hepatic L-02 cell line and peripheral blood mononuclear cells (PBMCs) were also evaluated since a potential anticancer drug candidate would be better to show selective cytotoxicity between malignant and normal cells.…”
Section: Antiproliferative Activitymentioning
confidence: 99%
“…The applied 5-FU doses were in line with previous studies of Novak et al . [ 44 ] and Gajski et al . [ 45 ], who also found that doses up to 250 μM are non-toxic for HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%